2003
DOI: 10.1038/nature01498
|View full text |Cite
|
Sign up to set email alerts
|

An enhanced cosmic-ray flux towards ζ Persei inferred from a laboratory study of the H3+–e- recombination rate

Abstract: The H3+ molecular ion plays a fundamental role in interstellar chemistry, as it initiates a network of chemical reactions that produce many molecules. In dense interstellar clouds, the H3+ abundance is understood using a simple chemical model, from which observations of H3+ yield valuable estimates of cloud path length, density and temperature. But observations of diffuse clouds have suggested that H3+ is considerably more abundant than expected from the chemical models. Models of diffuse clouds have, however,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
320
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(343 citation statements)
references
References 29 publications
16
320
6
Order By: Relevance
“…The discovery of significant abundances of H + 3 in diffuse clouds (McCall et al 1998), confirmed by follow-up detections (Geballe et al 1999;McCall et al 2003;Indriolo et al 2007), has led to values of ζ H 2 larger by about one order of magnitude than both the "standard" rate and previous estimates based on the abundance of OH and HD in dense clouds. Given the relative simplicity of the chemistry of H + 3 , it is now believed that diffuse clouds are characterized by CR ionization rates ζ H 2 ≈ 2 × 10 −16 s −1 or larger.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The discovery of significant abundances of H + 3 in diffuse clouds (McCall et al 1998), confirmed by follow-up detections (Geballe et al 1999;McCall et al 2003;Indriolo et al 2007), has led to values of ζ H 2 larger by about one order of magnitude than both the "standard" rate and previous estimates based on the abundance of OH and HD in dense clouds. Given the relative simplicity of the chemistry of H + 3 , it is now believed that diffuse clouds are characterized by CR ionization rates ζ H 2 ≈ 2 × 10 −16 s −1 or larger.…”
Section: Introductionmentioning
confidence: 77%
“…This high value of ζ H 2 in the diffuse interstellar gas can be reconciled with the lower values measured in cloud cores and massive protostellar envelopes by invoking various mechanisms of CR screening in molecular clouds due to either self-generated Alfvén waves in the plasma (Skilling & Strong 1976;Hartquist et al 1978;Padoan & Scalo 2005) or to magnetic mirror effects (Cesarsky & Völk 1978;Chandran 2000). An alternative explanation, based on the possible existence of a low-energy flux of CR particles, is that they can penetrate (and ionize) diffuse clouds but not dense clouds, as recently proposed by McCall et al (2003), see also Takayanagi (1973) and Umebayashi & Nakano (1981). This latter scenario is explored quantitatively in the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…Rate coefficients in 10-30 K gas are typically 10 −7 to 10 −6 cm 3 s −1 . The dissociative recombination of H + 3 , a key species in the chemistry, has been subject to considerable discussion in the last three decades, but experiments appear to converge on a rapid value of ∼ 10 −6 cm 3 s −1 at low temperatures 121 .…”
Section: Destructionmentioning
confidence: 99%
“…Spectroscopy of H + 3 at 3.5 µm toward a local diffuse cloud (McCall et al 2003) indicates a local enhancement of ζ CR relative to the above value by about a factor of 10, taking the distribution of species along the line of sight into account (Le Petit et al 2004). On the other hand, observations of emission lines of DCO + and other ions toward highly shielded pre-stellar cores indicate 8…”
Section: Cosmic-ray Ionizationmentioning
confidence: 99%